Aprendizagem Baseada na Resolução de Problemas: uma experiência educacional no estudo do perfil químico dos resíduos agroindustriais da Piper Nigrum L. - Lucas, Danielle dos Reis (2020)
This educational research is about the characterization of the chemical profile of agro-industrial waste produced from Piper Nigrum L. production by gas chromatography−mass spectrometry (GC-MS) and Fourier Transform Ion Cyclotron mass spectrometry (